Outdoor air pollution, green space, and cancer incidence in Saxony: a semi-individual cohort study - Thomas Datzmann; Iana Markevych; Freya Trautmann; Joachim Heinrich; Jochen Schmitt; Falko Tesch (BMC, 2018)
Abstract Background There are a few epidemiological studies that (1) link increased ambient air pollution (AP) with an increase in lung cancer incidence rates and (2) investigate whether residing in green spaces could be protective against cancer. However, it is completely unclear whether other forms of cancer are also affected by AP and if residential green spaces could lower cancer incidence rates in general. Therefore, the objective was to estimate whether AP and green space are associated with several cancer types. Methods The analysis was based on routine health care data from around 1.9 million people from Saxony who were free of cancer in 2008 and 2009. Incident cancer cases (2010-2014) of mouth and throat, skin (non-melanoma skin cancer - NMSC), prostate, breast, and colorectum were defined as: (1) one inpatient diagnosis, or (2) two outpatient diagnoses in two different quarters within one year and a specific treatment or death within two quarters after the diagnosis. Exposures, derived from freely available 3rd party data, included particulate matter with aerodynamic diameter of less than 10 μm (PM10) and nitrogen dioxide (N02) as well as green space (Normalized Difference Vegetation Index - NDVI). Associations between air pollutants, green space, and cancer incidence were assessed by multilevel Poisson models. Age, sex, physician contacts, short- and long-term unemployment, population density, and having an alcohol-related disorder were considered as potential confounders. Results Three thousand one hundred seven people developed mouth and throat cancer, 33,178 NMSC, 9611 prostate cancer, 9577 breast cancer, and 11,975 colorectal cancer during the follow-up period (2010-2014). An increase in PM10 of 10 μg/m3 was associated with a 53% increase in relative risk (RR) of mouth and throat cancer and a 52% increase in RR of NMSC. Prostate and breast cancer were modestly associated with PM10 with an increase in RR of 23 and 19%, respectively. The associations with N02 were in the same direction as PM10 but the effect estimates were much lower (7-24%). A 10% increase in NDVI was most protective of mouth and throat cancer (− 11% RR) and of NMSC (− 16% RR). Colorectal cancer was not affected by any of the exposures. Conclusions In addition to the studies carried out so far, this study was able to provide evidence that higher ambient AP levels increase the risk of mouth and throat cancer as well as of NMSC and that a higher residential green space level might have a protective effect for NMSC in areas with low to moderate UV intensity. Nevertheless, we cannot rule out residual confounding by socioeconomic or smoking status.